Experimental Analysis of Bamboo Strip Perforation Geometry on the Impact Response and Water Absorption of Epoxy Composites - Muhammad Abiyyu Hafizh Harahap; Kriswanto; Muhammad Irfan Nuryanta (Universitas Negeri Semarang, 2026)
Local geometric modification of natural fiber reinforcement offers a non-chemical route for tailoring compositebehavior, but the effect of perforating bamboo strips on mechanical response and moisture uptake remainsinsufficiently resolved. This study experimentally evaluated the influence of bamboo-strip perforationgeometry on the impact response and short-term water absorption of epoxy composites. Three-layer cottonfiber, bamboo strip, and cotton fiber laminates were fabricated by hand lay-up. Charpy impact testing, adaptedfrom ASTM D6110, compared perforation diameters of 0, 3.2, 4, and 6 mm, while water absorption testing,adapted from ASTM D570, compared 0, 1, 2, and 3 perforations of 3.2 mm diameter after 1, 2, and 3 h ofimmersion five specimens were tested for each variation. Impact strength showed a non-monotonic response,reaching 200.1 kJ/m² at 6 mm and 157.71 kJ/m² at 4 mm. Water absorption increased with immersion timein all configurations, while the one and three perforation configurations generally produced lower mean valuesthan the unperforated control. The results show that perforation geometry should be treated as a configurationdependent, multi response design variable rather than a uniformly beneficial interfacial modification.Microstructural characterization and inferential analysis are required to verify the mechanisms underlyingthese trends and their statistical robustness.